2018
DOI: 10.1098/rsob.180132
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Reduced interleukin-38 in non-small cell lung cancer is associated with tumour progression

Abstract: Lung cancer continues to be the leading cause of cancer-related deaths worldwide due to its high incidence, malignant behaviour and lack of major advancements in treatment strategy. The occurrence and development of lung cancer is closely related to inflammation. Thus, we conducted the present study to investigate the effects of IL-38 (interleukin-38), a newly identified anti-inflammatory factor, on non-small cell lung cancer (NSCLC), which accounts for about 85% of all lung cancers. We first evaluated the IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…However, they also found that IL-6 production in human Mφs was significantly increased by full-length IL-38 (aa1–152) ranging from 0 to 20 ng/mL, especially at 20 and 10 ng/mL, stimulated by IL-1β or LPS, full-length IL-38 (10 ng/mL) was also capable of decreasing IL-6 and IL-8 levels when Mφs were exposed to ACM. In another study, Wang and colleagues [129] found that IL-38 suppresses the migration, invasion, and growth of non-small cell lung cancer cells in a dose-dependent manner at a concentration ranging from 0 to 100 ng/mL. Zhang and colleagues [59] reported that IL-38 suppresses VEGF-induced proliferation and migration of endothelial cells at a concentration of 1 or 5 ng/mL, and Yuan and colleagues [15] reported that IL-17, TNF-α, IL-1β, and MCP-1 mRNA levels were inhibited by IL-38 at concentrations of 20 ng/mL in THP-1 cells exposed to LPS.…”
Section: Discussionmentioning
confidence: 99%
“…However, they also found that IL-6 production in human Mφs was significantly increased by full-length IL-38 (aa1–152) ranging from 0 to 20 ng/mL, especially at 20 and 10 ng/mL, stimulated by IL-1β or LPS, full-length IL-38 (10 ng/mL) was also capable of decreasing IL-6 and IL-8 levels when Mφs were exposed to ACM. In another study, Wang and colleagues [129] found that IL-38 suppresses the migration, invasion, and growth of non-small cell lung cancer cells in a dose-dependent manner at a concentration ranging from 0 to 100 ng/mL. Zhang and colleagues [59] reported that IL-38 suppresses VEGF-induced proliferation and migration of endothelial cells at a concentration of 1 or 5 ng/mL, and Yuan and colleagues [15] reported that IL-17, TNF-α, IL-1β, and MCP-1 mRNA levels were inhibited by IL-38 at concentrations of 20 ng/mL in THP-1 cells exposed to LPS.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Wang et al demonstrated that IL-38 expression is decreased in NSCLC alone relative to adjacent non-tumor tissue (150), with lack of IL-38 expression correlating with poor prognosis. Administration of recombinant IL-38 inhibited β-catenin expression and reduced the proliferation, migration and invasion of lung cancer cells in vitro , while increasing cell death.…”
Section: Interleukin-38mentioning
confidence: 96%
“…In contrast, there is much less information about the effects of pyroptosis. As a foreign composition in an organism, NSCLC cells predispose to initiate an autoimmune response and in turn trigger a series of inflammatory cascade [7]. Given these evidence, we thereby hypothesized that pyroptosis possesses a tight correlation with the progression of NSCLC.…”
Section: Introductionmentioning
confidence: 99%